A proteomic study of the pulmonary injury induced by microcystin-LR in mice. (August 2018) - Zhao, Sujuan; Sun, Hong; Yan, Wei; Xu, Dexiang; Shen, Tong
Abstract: MCLR has been shown to act as potent hepatotoxin, and recent studies showed that MCs can accumulate in lung tissue and exert adverse effects. However, the exact mechanism still remain unclear. The present study mainly focuses on the impairments of respiratory system after MCLR exposure in mice. After intratracheal instillation with MCLR (0, 10 and 25 μg/kg bw), histological change was examined in MCLR exposure groups. Results indicated that exposure of MCLR led to serious histopathology alteration and apoptosis in lung of mice. To further our understanding of the toxic effects of MCLR on the lung, we employed a proteomic method to search the mechanisms behind MCLR-induced pulmonary injury. In total, 38 proteins were identified to be significantly altered after MCLR exposure. These proteins involved in inflammatory response, apoptosis, cytoskeleton, and energetic metabolism, suggesting MCLR exerts complex toxic effects contributing to pulmonary injury. Furthermore, MCLR also induced pulmonary inflammation, as manifested by up-regulating the protein levels of interleukin-1β (IL-1β) and p65 subunit. Our results indicated that MCLR exerts lung injury mainly by generating inflammation and apoptosis. Graphical abstract: Image 1 Highlights: MCLR can accumulate in lungs and induce lung injury. Proteomics results revealed that 38 proteins expression were markedly altered. MCLR exerts lung injury mainly by generating inflammation and apoptosis.